Water-based anticorrosive paint for construction with rust and preparation method of water-based anticorrosive paint

By preparing rust-based anticorrosion coatings containing components such as aqueous epoxy resin emulsion, the corrosion resistance and construction convenience of coatings in harsh underground environments are solved, and effective anticorrosion effect under humid and acid-base conditions is achieved.

CN120536023APending Publication Date: 2025-08-26SHANDONG LABOR VOCATIONAL & TECHN COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510830574.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Existing paints are difficult to effectively resist corrosion in harsh underground environments, especially corrosion under damp and acid-base conditions, and thermosetting paints are inconvenient in on-site construction.

Method used

The water-based anticorrosion coating is used to construct rust, including components A and components B. The components include aqueous epoxy resin emulsion, sheet zinc, spherical zinc, nanocarbon powder, shell powder, cellulose, nanoTC4 powder, polytetrafluoroethylene powder and nanoTiO2, etc. The coating is prepared through specific stirring and mixing processes to form a uniform protective film.

Benefits of technology

The coating exhibits good corrosion resistance, film formation and operational convenience in the underground environment, which can effectively prevent corrosion of steel structures and metal components, and is suitable for moisture and acid-base conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120536023A_ABST
    Figure CN120536023A_ABST
Patent Text Reader

Abstract

The invention discloses waterborne anticorrosive paint for construction with rust and a preparation method of the waterborne anticorrosive paint, and belongs to the technical field of paint and processing. The water-based anticorrosive paint for construction with rust is characterized by comprising a component A and a component B, the component A is prepared from the following components in parts by weight: 28 to 42 parts of waterborne epoxy resin emulsion, 10 to 24 parts of flaky zinc, 18 to 30 parts of spherical zinc, 1.2 to 5.8 parts of flatting agent, 0.8 to 6.8 parts of nano carbon powder, 9.2 to 18.4 parts of shell powder, 0.6 to 3.8 parts of cellulose, 0.8 to 2.4 parts of nano TC4 powder, 0.48 to 3.8 parts of polytetrafluoroethylene powder and 1.2 to 5.8 parts of nano TiO2; and the component B is 10-30 parts by weight of a curing agent. The coating capable of resisting the severe underground environment is prepared by reasonably selecting the coating materials, proportioning the components and reasonably controlling the technological process, and has the characteristics of high salt corrosion resistance, high humidity corrosion resistance, good acid and alkali resistance, low cost, good film-forming property and convenience in operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and processing, and particularly relates to a water-based anti-corrosion coating for rust-resistant construction and a preparation method thereof. Background Art

[0002] With the development of mineral resources such as oil and coal, a large number of mines have emerged. The formation fluid contains sulfide, carbon dioxide, chloride ions, water and microorganisms and other corrosive components, which cause serious corrosion of steel structures and metal components used in underground operations, affecting normal operations. Paint application is the most common on-site corrosion protection method for steel structures. Most paints are typically thermosetting, which cure when a functional resin reacts with a cross-linking material that has functional groups that react with the resin's functional groups. Different paints require different modifications depending on the environment in which they will be used.

[0003] Steel structures and metal components used in underground operations are often exposed to humid, acidic and alkaline environments. Therefore, those skilled in the art have been researching coatings that can withstand the harsh underground environment. Summary of the Invention

[0004] In response to the problems existing in the prior art, the present invention provides a water-based anti-corrosion coating for rust-resistant construction and a preparation method thereof, which can better meet the needs of the coating for anti-corrosion operations in underground coal mines.

[0005] The present invention is achieved through the following technical solutions: A water-based anti-corrosion coating for rust-resistant construction, comprising component A and component B; The component A comprises the following components in parts by weight: 28-42 parts of waterborne epoxy resin emulsion, 10-24 parts of flaky zinc, 18-30 parts of spherical zinc, 1.2-5.8 parts of leveling agent, 0.8-6.8 parts of nano carbon powder, 9.2-18.4 parts of shell powder, 0.6-3.8 parts of cellulose, 0.8-2.4 parts of nano TC4 powder, 0.48-3.8 parts of polytetrafluoroethylene powder, and 1.2-5.8 parts of nano TiO2; The B component is 10 to 30 parts by weight of a curing agent.

[0006] Furthermore, the size of the flaky zinc is 500-600 mesh; the size of the spherical zinc is 800-1000 mesh; and the size of the shell powder is 400-500 mesh.

[0007] Furthermore, the size of the polytetrafluoroethylene powder is 800-1000 mesh.

[0008] Furthermore, the leveling agent is an associative polyurethane leveling agent; the curing agent is an amine curing agent and the curing agent is polyamide.

[0009] Furthermore, the cellulose is hydroxypropyl methylcellulose.

[0010] In the present invention, the preparation method of the water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix and stir water-based epoxy resin emulsion, zinc flakes, zinc sphericals, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components, add leveling agent during the stirring process, and mix well to obtain component A; (2) Component A and component B are mixed and stirred to obtain a water-based anti-corrosion coating for rust-resistant construction.

[0011] Furthermore, in step (1), the stirring speed is 400-500 r / min, the stirring time is 3-5 h, and the mixture is left to stand for 24 h.

[0012] Furthermore, in step (1), the stirring speed is 400-500 r / min, and the stirring time is 90-120 min.

[0013] Nano TC4 powder has a nano effect and is relatively evenly distributed in the paint. It is easily affected by the external environment and forms a TiO2 protective film, thereby improving the corrosion resistance of the paint. The added shell powder is the mantle of a mollusk living near the water, which is mainly composed of an inorganic phase and an organic phase. The inorganic phase is CaCO3, and the organic phase is composed of organic matter such as protein. It has good corrosion resistance and can enhance the flexibility and smoothness of the material surface without cracking. At room temperature, cellulose is insoluble in water and general organic solvents, its molecules are polar, and the interaction force between molecular chains is very strong, which can effectively reduce the agglomeration of nano molecules. Nano carbon powder and polytetrafluoroethylene powder work synergistically to improve the fluidity and transparency of the paint, giving the paint excellent color.

[0014] Beneficial effects The present invention prepares a coating that can withstand the harsh environment of the underground mine through the reasonable selection of coating materials and the ratio of components, and then through the reasonable control of the process. The coating has the characteristics of high salt corrosion resistance, high humidity corrosion resistance, good acid and alkali resistance, low cost, good film-forming properties, and easy operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is an SEM image of the coating surface after curing of the water-based anti-corrosion coating of Example 1; Figure 2 This is an SEM image of the coating surface after curing of the water-based anti-corrosion coating of Example 2; Figure 3 This is an SEM image of the coating cross section after the water-based anti-corrosion coating of Example 3 is cured. DETAILED DESCRIPTION

[0016] The present invention is described below with reference to examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.

[0017] The raw materials in the present invention are water-based epoxy resin emulsion, flaky zinc, spherical zinc, associative polyurethane leveling agent, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2, and polyamide, all of which are commercially purchased products.

[0018] The parts in the following examples are parts by weight.

[0019] Example 1 The composition of water-based anti-corrosion coating for rust construction includes component A and component B: Component A: 28 parts of water-based epoxy resin emulsion, 14 parts of 500-600 mesh flaky zinc, 20 parts of 800-1000 mesh spherical zinc, 2.4 parts of associative polyurethane leveling agent, 2.6 parts of nano-carbon powder, 12.4 parts of 400-500 mesh shell powder, 1.2 parts of cellulose, 1.6 parts of nano-TC4 powder, 1.8 parts of 800-1000 mesh polytetrafluoroethylene powder, and 2.0 parts of nano-TiO2; Component B: 10 parts of curing agent polyamide; The preparation method of a water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix and stir water-based epoxy resin emulsion, zinc flakes, zinc spheres, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components. Add leveling agent during the stirring process. The stirring speed is 400 r / min and the stirring time is 3 h. After mixing evenly, component A is obtained. Observe that the components of the coating are evenly dispersed and leave it for 24 h for use. (2) Component A and component B are mixed and stirred at a stirring speed of 400 r / min for 90 min to obtain a water-based anti-corrosion coating for rust-resistant construction; (3) Prepare the test substrate, polish it with 200#-600# sandpaper, then clean the surface of the substrate with acetone solution and ethanol solution to remove the dirt on the surface of the substrate, put it into a vacuum drying oven for drying at 80℃ for 15 minutes, and then set aside; (4) Use a special paint brush or sprayer to evenly apply the paint on the surface of the substrate. The surface of the substrate should be even, flat and without dead corners. Place it at a temperature of 25±2℃ for 48 hours; (5) The surface morphology of the substrate coating was observed using SEM. The coating surface had no cracks, good film formation, relatively uniform distribution of solid powder, and no agglomeration. The SEM image of the coating surface after curing was as follows: Figure 1 shown.

[0020] Example 2 The composition of water-based anti-corrosion coating for rust construction includes component A and component B: Component A: 32 parts of waterborne epoxy resin emulsion, 18 parts of 500-600 mesh flaky zinc, 28 parts of 800-1000 mesh spherical zinc, 4.2 parts of associative polyurethane leveling agent, 4.6 parts of nano-carbon powder, 15.2 parts of 400-500 mesh shell powder, 2.4 parts of cellulose, 1.0 part of nano-TC4 powder, 2.0 parts of 800-1000 mesh polytetrafluoroethylene powder, and 3.6 parts of nano-TiO2; Component B: 20 ​​parts of curing agent polyamide; The preparation method of a water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix and stir water-based epoxy resin emulsion, flaky zinc, spherical zinc, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components. Add leveling agent during the stirring process. The stirring speed is 450 r / min and the stirring time is 4 h. After mixing evenly, component A is obtained. Observe that the components of the coating are evenly dispersed and leave it for 24 h for use. (2) Component A and component B are mixed and stirred at a stirring speed of 450 r / min for 100 min to obtain a water-based anti-corrosion coating for rust-resistant construction; (3) Prepare the test substrate, polish it with 200#-600# sandpaper, then clean the surface of the substrate with acetone solution and ethanol solution to remove the dirt on the surface of the substrate, put it into a vacuum drying oven for drying at 80℃ for 20min, and then set aside; (4) Use a special paint brush or sprayer to evenly apply the paint on the surface of the substrate. The surface of the substrate should be even, flat and without dead corners. Place it at a temperature of 25±2℃ for 48 hours; (5) The surface morphology of the substrate coating was observed using SEM. The coating surface had no cracks, good film formation, relatively uniform distribution of solid powder, and no agglomeration. The SEM image of the coating surface after curing was as follows: Figure 2 shown.

[0021] Example 3 The composition of water-based anti-corrosion coating for rust construction includes component A and component B: Component A: 42 parts of waterborne epoxy resin emulsion, 20 parts of 500-600 mesh flaky zinc, 26 parts of 800-1000 mesh spherical zinc, 4.8 parts of associative polyurethane leveling agent, 4.8 parts of nano-carbon powder, 18.4 parts of 400-500 mesh shell powder, 2.4 parts of cellulose, 1.8 parts of nano-TC4 powder, 2.1 parts of 800-1000 mesh polytetrafluoroethylene powder, and 3.6 parts of nano-TiO2; Component B: 30 parts of curing agent polyamide; The preparation method of a water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix water-based epoxy resin emulsion, flaky zinc, spherical zinc, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components, add leveling agent during the stirring process, stir at a speed of 500 r / min, stir for 5 h, and mix well to obtain component A. Observe that the components of the coating are evenly dispersed and leave it for 24 h for use; (2) Component A and component B are mixed and stirred at a stirring speed of 500 r / min for 120 min to obtain a water-based anti-corrosion coating for rust-resistant construction; (3) Prepare the test substrate, polish it with 200#-600# sandpaper, then clean the surface of the substrate with acetone solution and ethanol solution to remove the dirt on the surface of the substrate, put it into a vacuum drying oven for drying at 80℃ for 30min, and then set aside; (4) Use a special paint brush or sprayer to evenly apply the paint on the surface of the substrate. The surface of the substrate should be even, flat and without dead corners. Place it at a temperature of 25±2℃ for 48 hours; (5) The surface morphology of the substrate coating was observed using SEM. The coating surface had no cracks, the solid powder was evenly distributed, and there was no agglomeration. The SEM image of the coating surface after curing was as follows: Figure 3 As shown, it indicates good film-forming properties.

[0022] Comparative Example 1 A waterborne epoxy zinc-rich coating is composed of a component A and a component B, wherein component A comprises the following substances in parts by weight: 50 parts of a waterborne epoxy emulsion, 20 parts of zinc powder, and 1 part of an associative polyurethane leveling agent; component B is 20 parts by weight of a curing agent polyamide; the prepared coating is operated as in Example 1 and coated on a substrate for performance testing.

[0023] Comparative Example 2 The composition of water-based anti-corrosion coating for rust construction includes component A and component B: Component A: 28 parts of water-based epoxy resin emulsion, 14 parts of 500-600 mesh flaky zinc, 20 parts of 800-1000 mesh spherical zinc, 2.4 parts of associative polyurethane leveling agent, 2.6 parts of nano-carbon powder, 14 parts of 400-500 mesh shell powder, 1.2 parts of cellulose, 1.8 parts of 800-1000 mesh polytetrafluoroethylene powder, and 2.0 parts of nano-TiO2; Component B: 10 parts of curing agent polyamide; The preparation method of a water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix and stir water-based epoxy resin emulsion, zinc flakes, zinc spheres, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components. Add leveling agent during the stirring process. The stirring speed is 400 r / min and the stirring time is 3 h. After mixing evenly, component A is obtained. Observe that the components of the coating are evenly dispersed and leave it for 24 h for use. (2) Component A and component B were mixed and stirred at a stirring speed of 400 r / min for 90 min to obtain an anti-corrosion coating. The prepared coating was operated as in Example 1 and coated on a substrate for performance testing.

[0024] Comparative Example 3 The composition of water-based anti-corrosion coating for rust construction includes component A and component B: Component A: 28 parts of water-based epoxy resin emulsion, 14 parts of 500-600 mesh flaky zinc, 20 parts of 800-1000 mesh spherical zinc, 2.4 parts of associative polyurethane leveling agent, 2.6 parts of nano-carbon powder, 1.2 parts of cellulose, 1.8 parts of 800-1000 mesh polytetrafluoroethylene powder, and 2.0 parts of nano-TiO2; Component B: 10 parts of curing agent polyamide; The preparation method of a water-based anti-corrosion coating for rust-resistant construction comprises the following steps: (1) Mix and stir water-based epoxy resin emulsion, zinc flakes, zinc spheres, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components. Add leveling agent during the stirring process. The stirring speed is 400 r / min and the stirring time is 3 h. After mixing evenly, component A is obtained. Observe that the components of the coating are evenly dispersed and leave it for 24 h for use. (2) Component A and component B were mixed and stirred at a stirring speed of 400 r / min for 90 min to obtain an anti-corrosion coating. The prepared coating was operated as in Example 1 and coated on a substrate for performance testing.

[0025] The coating's pull-off strength, salt spray test and other properties were tested in accordance with GB / T5210-2006, GB / T10125-2021 and other standards. The test results are shown in Table 1: Table 1. Coating properties of Examples 1-3 and Comparative Examples 1-3 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A water-based anti-corrosion coating for rust construction, characterized in that: It includes component A and component B; The component A comprises the following components in parts by weight: 28-42 parts of waterborne epoxy resin emulsion, 10-24 parts of flaky zinc, 18-30 parts of spherical zinc, 1.2-5.8 parts of leveling agent, 0.8-6.8 parts of nano carbon powder, 9.2-18.4 parts of shell powder, 0.6-3.8 parts of cellulose, 0.8-2.4 parts of nano TC4 powder, 0.48-3.8 parts of polytetrafluoroethylene powder, and 1.2-5.8 parts of nano TiO2; The B component is 10 to 30 parts by weight of a curing agent.

2. The water-based anti-corrosion coating for rust-proof construction according to claim 1, characterized in that: The size of the flaky zinc is 500-600 mesh; the size of the spherical zinc is 800-1000 mesh; and the size of the shell powder is 400-500 mesh.

3. The water-based anti-corrosion coating for rust-proof construction according to claim 1, characterized in that: The size of the polytetrafluoroethylene powder is 800-1000 meshes.

4. The water-based anti-corrosion coating for rust-proof construction according to claim 1, characterized in that: The leveling agent is an associative polyurethane leveling agent; the curing agent is an amine curing agent and the curing agent is polyamide.

5. The water-based anti-corrosion coating for rust-proof construction according to claim 1, characterized in that: The cellulose is hydroxypropyl methylcellulose.

6. A method for preparing a water-based anti-corrosion coating for rust-resistant construction according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mix and stir water-based epoxy resin emulsion, zinc flakes, zinc sphericals, nano carbon powder, shell powder, cellulose, nano TC4 powder, polytetrafluoroethylene powder, nano TiO2 and other components, add leveling agent during the stirring process, and mix well to obtain component A; (2) Component A and component B are mixed and stirred to obtain a water-based anti-corrosion coating for rust-resistant construction.

7. The method for preparing a water-based anti-corrosion coating for rust-resistant construction according to claim 6, wherein: In step (1), the stirring speed is 400-500 r / min, the stirring time is 3-5 h, and the mixture is placed for 24 h for standby use.

8. The method for preparing a water-based anti-corrosion coating for rust-resistant construction according to claim 6, wherein: In step (1), the stirring speed is 400-500 r / min and the stirring time is 90-120 min.